Fish vaccination - Gudding, Roar; Lillehaug, Atle; Evensen, Øystein (Wiley-Blackwell, 2014)
Fish farming, in seawater and in freshwater, in cages, tanks or ponds, makes an ever-increasing and significant contribution to the production of aquatic food in many regions of the world. During the last few decades there has been significant progress and expansion in the aquaculture sector, characterized by intensified production and the exploitation of many new species. Aquaculture must be a sustainable bio-production, environmentally as well as economically. Disease prevention in order to reduce losses, and the use of antimicrobials is crucial in this perspective. Vaccination has, in a few years, become the most important method for disease prevention in aquaculture, and effective prophylaxis based on stimulation of the immune system of the fish is essential for further development of the industry. This book provides general information about disease prevention in fish by vaccination, as well as specific descriptions of the correct use of vaccines against the most important bacterial and viral infectious diseases of aquatic animals. The book is written by some of the world's leading experts in the subject, drawn from many countries where aquaculture is a significant and expanding part of the economy. Fish Vaccination is an encyclopedia of fish vaccinology for every present and future aquaculturist. Professionals in the aquaculture sector, including fish veterinarians and fish biologists, within the industry, in scientific institutions and regulatory authorities will all find a huge wealth of commercially important knowledge within this book. Libraries in all universities where aquaculture, biological and veterinary sciences are studied and taught should have copies of this important book on their shelves.